Multi-switching synchronization of chaotic systems with active controllers - Ucar, Ahmet; Lonngren, Karl E.; Bai, Er-Wei (Pergamon-Elsevier Science Ltd, 2008)
This paper reports the results of an investigation of the multi-switching synchronization of coupled chaotic systems via active controls. The synchronization is achieved with the slave-master scheme, and it is extended to investigate the synchronization problems with different combinations of slave states with master systems. The different active controller are designed for the chosen slave system states to be synchronized with the target master system states. The multi-switching synchronization of Lorenz system is considered. Numerical simulations are provided for illustration and verification of the proposed method. (C) 2006 Published by Elsevier Ltd.
Keywords: Lorenz Systems